PENGGUNAAN BAHASA GAUL DALAM KOMENTAR INSTAGRAM GIBRAN RAKA BUMING RAKA PADA KAMPANYE WAKIL PRESIDEN 2024 - Yesi Ratna Sari; Eli Rustinar; Jelita Zakaria; Yanti Paulina; Ira Yuniati (Universitas Sultan Ageng Tirtayasa, 2026)
The problem addressed in this study is how slang and the functions of slang appear on Gibran Raka Buming Raka's Instagram account in relation to the 2024 vice presidential election. The purpose of this study is to describe the forms of slang and the functions of slang found in comments on Gibran Raka Buming Raka's (GRBR) Instagram account during the 2024 vice presidential campaign. The background of this research is based on the phenomenon of increasing slang usage on social media, especially in political situations that are usually formal in nature. The method applied in this research is descriptive qualitative with data collection techniques through observation and documentation, screenshots, and comments from informants between February and August 2024. The findings of the study indicate that the slang language used can be classified into four categories: abbreviations, acronyms, and creative forms. The functions of slang language include fostering closeness in relationships, group solidarity, shifting the topic of conversation, expressing humor, group identity, and enjoyment. Based on the findings and analysis, there are a total of 40 instances of slang language in this study.